Dual‐expansion indexing for moving objects. Issue 2 (1st April 2014) - Shen, Jun-Hong; Chang, Ye-In; Chang, Fang-Ming
Abstract : With the development of wireless communications and mobile computing technologies, the applications of moving objects have been developed in many topics, for example, traffic monitoring. Such applications need to track the current and near‐future locations of the moving objects. This motivates the development of spatial‐temporal indices to support efficient querying about such locations of the moving objects. Therefore, in this study, the authors propose a dual‐expansion indexing (DEI) to support the current and near‐future prediction of the moving objects. To filter out more number of the data blocks that do not contain the final result, the query region can be expanded in each of eight directions individually. To further reduce the number of the data blocks that should be examined, the qualified data blocks can be expanded according to the direction towards the query region. Moreover, only the objects moving to the query region will be checked in the query process of DEI. Therefore our method can reduce more number of retrieved data blocks and that of input/output operations than the existing method. Experimental results show that the query process of DEI is more efficient than that of the existing method.